Inheritance tax-exempt transfer of German businesses: Imperative or unjustified subsidy? An empirical analysis - Henriette Houben; Ralf Maiterth (Arbeitskreis Quantitative Steuerlehre (arqus), 2009)
This contribution addresses the substantial tax subsidies for businesses introduced by the German Inheritance Tax Act 2009. Advocates in favour of the vast or even entire tax exemption for businesses stress the potential damage of the inheritance tax on businesses, as those often lack liquid assets to meet tax liability. This submission tackles this issue empirically based on data of the German Inheritance Tax Statistics and the SOEP. The results indicate that former German inheritance tax law has not endangered transferred businesses. Hence, there is no need for the tremendous tax privilege for businesses in current German inheritance tax law. A virtual uniformed inheritance tax without tax privileges, which meets revenue neutrality per tax class according to current tax law, provokes in some cases relative high tax loads which might trouble businesses.
Keywords: 330; Erbschaftsteuer; Steuerbegünstigung; Unternehmensbesteuerung; Unternehmensnachfolge; Steuerbelastung; Besteuerungsgrundsatz; Deutschland